PECULIARITIES OF THE TRANSLATION OF PHRASEOLOGY - Bakhodir Pirmuhamedov (Zeta Repository, 2023)
Phraseology as a separate scientific discipline first appeared in the former Soviet Union in the 1960s of the 20th century. The founder of this science is V.V. Vinogradov. In his rese arch, he clearly established the concept of phraseologism. In them, the scientist revealed the classification of phraseological units and determined the main directions for studying phraseology for many years. After that, sciences in this direction appeare d in Europe, especially in Germany, where the influence of Soviet phraseology was very strong.